Exploring the antecedents of AI adoption for effective HRM practices in the Indian pharmaceutical sector - Goswami, Manisha; Jain, Supriya; Alam, Tabish; Deifalla, Ahmed Farouk; Ragab, Adham E.; Khargotra, Rohit (Frontiers in Pharmacology, 2023)
The aim of this research is to investigate the factors that facilitate the adoption of Artificial Intelligence (AI) in order to establish effective human resource management (HRM) practices within the Indian pharmaceutical sector.A model explaining the antecedents of AI adoption for building effective HRM practices in Indian Pharma Sector is proposed in this study. The proposed model is based on task technology fit theory.To test the model, a two-step procedure known as partial least squares structural equational modelling (PLS SEM) was used. To collect data, 160 HRM employees from pharmacy firms from pan India were approached. Only senior and specialized HRM positions were sought.An examination of the relevant literature reveals that factors such as how prepared an organization is, how people perceive the benefits, and how technological readiness influence AI adoption. As a result, HR systems may become more efficient. The PLS-SEM data support all the mediation hypothesized proving full and partial mediation both, demonstrating the accuracy of the proposed model.There has been little prior research on the topic, this study adds a great deal to our understanding of what motivates human resource departments to adopt AI in Pharmaceutical Companies of India. Furthermore, AI-related recommendations are made to HRM based on the results of a statistical analysis.